PENAMBAHAN KULIT ARI BIJI KEDELAI HASIL FERMENTASI MENGGUNAKAN EM-4 DALAM FORMULASI RANSUM PELLET BROILER TERHADAP FRAKSI SERAT - Anwar Efendi Harahap; Hidayati Hidayati; Sri Devi; Bakhendri Solfan (Fakultas Pertanian Universitas Veteran Bangun Nusantara Sukoharjo, 2020)
Source of feed raw materials can be obtained from various wastes, one of which is industrial waste is soybean seed, processing soybean seed, which has the potential as broiler ration in the form of pellets. This study aims to evaluate the fraction of broiler pellet fiber fermented soybean seed (KABKF) using Effective Microorganism-4 with different storage times. The research method used was an experimental method with a completely randomized design consisting of 5 treatments and 4 replications. The variables in this study were the fiber fraction content which included NDF (%), ADF (%), ADL (%), hemicellulose (%) and cellulose (%). The results of this study indicate that the longer the storage of broiler pellet rations can reduce the NDF content (75.50% - 53.31%), ADF (57.57% - 41.56%), and ADL (12.33% - 5.73%). ) and had not been able to increase the content of hemicellulose (11.86% - 17.93%) and cellulose (42.39-29.78%. The conclusion of this study is that 8 weeks of storage has the best treatment in reducing the content of NDF%, ADF%, and ADL%